Silenced Fighters: Identity, Language and Thought of the Nasa People in Bilingual Contexts of Colombia - Wilder Yesid Escobar Alméciga; July Carolina Gómez Lobatón (Profile Issues in Teachers' Professional Development, 2010)
This article is the result of a theoretical investigation and a reflection guided by a revision of literature and a set of interviews conducted of two members of the Nasa community: Adonias and Sindy Perdomo, father and daughter who belong to a Nasa sub-community located in Tierradentro, Cauca, southwestern Colombia. The article addresses three major factors. Firstly, it depicts identity processes that are constructed and constituted through language. Secondly, it explores the power structures perceived by two Nasa people, one of Colombia's minority groups. Finally, it identifies and connects correlating dots between the literature, the testimonies of Adonias and Sindy Perdomo and the teaching practices, approaches and beliefs in the area of ELT (English Language Teaching) in Colombia.